Challenges and opportunities in mapping land use intensity globally - Tobias Kuemmerle; Karlheinz Erb; Patrick Meyfroidt; Daniel Müller; Peter H Verburg; Stephan Estel; Helmut Haberl; Patrick Hostert; Martin R. Jepsen; Thomas Kastner; Christian Levers; Marcus Lindner; et al. (Current Opinion in Environmental Sustainability, 2013)
Future increases in land-based production will need to focus more on sustainably intensifying existing production systems. Unfortunately, our understanding of the global patterns of land use intensity is weak, partly because land use intensity is a complex, multidimensional term, and partly because we lack appropriate datasets to assess land use intensity across broad geographic extents. Here, we review the state of the art regarding approaches for mapping land use intensity and provide a comprehensive overview of available global-scale datasets on land use intensity. We also outline major challenges and opportunities for mapping land use intensity for cropland, grazing, and forestry systems, and identify key issues for future research.
Keywords: 330